Marginal note on wastewater recycling margins from the perspective of simultanism of sustainability and technological development - Kovács, Róbertné; Wang, Chao-Tang; Nagy, Valeria (COLUMELLA – Journal of Agricultural and Environmental Sciences, 2022)
The main feature of our time is the "duality": we demand livable environment, on the other hand we use it in anunsustainable way to ensure the overflowing comfort of welfare societies. As a result, the use of the environment– namely the environmental elements and their systems, processes and structures – has now led to overloading(pollution, damage). So the state of our habitats, reflects our actions, there is no doubt about that. That is, ouractivity is an imprint of our thinking. Changing/modification requires innovations that facilitate the developmentand application of the embedded technologies of the future, building on the intersubjectivity of individuals.One of the cornerstones of the European Green Deal is that "economic growth should be decoupled fromresource use". Among our resources, the water – especially drinking water – is a scarce commodity. However,with prudence, care and ingenuity, we can do a lot to reduce the amount of wastewater.Our short paper demonstrates, through an example of wastewater recyclability, that increasing volumes are nolonger just a problem to solve. Rather, it is a challenge, and technological development offers a way out of itstrap, so that the society does not have to face the negative effects of declining water supply.
Keywords: water; wastewater; utilization technology; possibilities